A case of primary squamous cell carcinoma of the breast with pathologic complete response after neoadjuvant chemotherapy - KAYA, HANDAN; YUMUK, PERRAN FULDEN; ÖNEŞ, TUNÇ (MOSBY-ELSEVIER, 2019)
Background: Primary squamous cell carcinoma (SCC) of the breast is a metaplastic carcinoma subtype which includes fibromatosis-like and sarcomatoid features. This is a very aggressive tumor with poor prognosis. Other sites of primary SCC should be ruled out first to classify these tumors as primary SCC of the breast. Here we present a case of locally advanced primary SCC of the breast. Case Report: A 72 years old woman presented with a right axillary lump. Trucut biopsy was performed, it showed squamous cell carcinoma. Estrogen receptor had poor immunoreactivity, negative for both progesteron receptor and HER 2 in immunohistochemistry staining. PETCT imaging were conducted to showing only 6 x 6.5 cm mass in right breast adjacent to axilla, multiple lymphadenomegaly in right axillary. We planned neoadjuvant chemotherapy consisting of weekly paclitaxel followed by epirubicin and cyclophosphamide combination. Postoperative pathology revealed wide necrosis, no viable tumor cell. We started adjuvant anastrozole treatment of 1 mg/day. No evidence of disease was detected after 1 year follow up. Conclusion: Primary squamous cell carcinoma of the breast is a very rare disease with no standard treatment approach. Our case achieved pathologic complete response after neoadjuvant chemotherapy. (C) 2018 Elsevier Inc. All rights reserved.
Keywords: Breast cancer; Neoadjuvant treatment; Rare tumor